A non-invasive technique for blood glucose measurement in periodontal patients - Falcón-Guerrero , Britto Ebert (2026)
Introduction:  The prevalence of diabetes in high-risk populations underscores the need for effective screening methods within the dental setting. Objectives: To determine the correlation between glucose levels obtained from gingival crevicular blood and capillary blood (finger prick) in diabetic patients with chronic gingival inflammation. Materials and Methods: An observational, descriptive, cross-sectional study was conducted. Seventy patients with diabetes presenting chronic periodontal disease and gingival inflammation were selected based on established inclusion criteria. Excess gingival crevicular blood from periodontal pockets was collected using glucometer test strips to determine each patient's glucose levels. Capillary blood was collected via finger prick, and glucose levels were measured using the same device. Venous blood was also collected for corresponding analysis. The relationship between variables was evaluated using the Pearson correlation coefficient. Results: A positive and highly significant correlation was found between glucose levels obtained from gingival crevicular blood and capillary blood (r = 0.982, p < 0.001). A strong correlation was also observed between gingival crevicular blood values and corrected venous blood glucose levels determined by conventional laboratory methods (r = 0.891, p < 0.001). Conclusions: A strong linear correlation exists between the evaluated methods; therefore, gingival crevicular blood analysis constitutes a useful and feasible tool for hyperglycemic screening.